1999
DOI: 10.15407/spqeo2.04.066
|View full text |Cite
|
Sign up to set email alerts
|

On problem of the rigorous diffraction quantitative description

Abstract: New data showing an inaccuracy of Kirchhoff's description for the diffraction of the limited aperture light beams are presented. A series of the known experimental facts, which did not have an unequivocal interpretation within the framework of this theory, gains a simple explanation with passage to conceptions of the rigorous diffraction theory. The difficulties hindering the wide application of this theory for solving practical problems are considered as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…The detection of structural anomalies in the far field of the single-mode Nd + : glass laser with plane mirrors and intracavity slit [2,3] gave the cause for the present article. Though these anomalies had obviously regular character, which had not been connected with the action of random factors, any explanation within the limits of existing theoretical conceptions [1,4,5] was not found.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…The detection of structural anomalies in the far field of the single-mode Nd + : glass laser with plane mirrors and intracavity slit [2,3] gave the cause for the present article. Though these anomalies had obviously regular character, which had not been connected with the action of random factors, any explanation within the limits of existing theoretical conceptions [1,4,5] was not found.…”
Section: Introductionmentioning
confidence: 77%
“…2b-c) changes by jump on one ring element with complete reorientation wave normals in the cavity. It is logical to suppose that the experimentally observed instability of the far field angular structure at monotonous change of the cavity aperture [2,3] is connected to this phenomenon as well.…”
Section: Effect Of Waveguide Trajectory Reorientationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the alternative boundary diffraction wave (BDW) approach, Maggi [17] and Rubinowicz [18] independently showed that the problem is equivalent to solving a line integral for the spherical waves generated at the hole boundary in addition to the geometry wave that passes through the hole without perturbation. This postulate was further developed by many scientists and applied to numerous problems such as plane wave propagation over a knife-edge or through a slit [20][21][22][23][24][25][26][27].…”
Section: Boundary Diffraction Wave To Describe the Far Fieldmentioning
confidence: 99%